Uniformly 2-absorbing primary ideals of commutative rings - Mostafanasab, H.; Tekir, Ü.; Ulucak, G. (Algebra and Discrete Mathematics, 2020)
In this study, we introduce the concept of “uniformly 2-absorbing primary ideals” of commutative rings, which imposes a certain boundedness condition on the usual notion of 2-absorbing primary ideals of commutative rings. Then we investigate some properties of uniformly 2-absorbing primary ideals of commutative rings with examples. Also, we investigate a specific kind of uniformly 2-absorbing primary ideals by the name of “special 2-absorbing primary ideals”